2000
DOI: 10.1080/11250000009356295
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of hand‐reared orphaned long‐eared owls and tawny owls after release in the wild

Abstract: Two groups of eight long-eared owls, Asio otus, and eight tawny owls, Strix aluco, which entered a Rehabilitation Centre as nestlings, were studied. When more than 60 days old they were released to the wild. The aim of this study concerns the analysis of their behaviour immediately after release and their adaptation to natural life. The owls were radio-tagged and followed continuously, also with direct observation, until they disappeared from the area or died. The long-eared owls, released in an agricultural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Their conclusion was that short-term survival (75%) was sufficient to justify the rehabilitation process. Csermely (2000a) tracked eight juvenile Tawny Owls for 7 -79 days, recorded only one death by predation and drew a similar conclusion to Bennett and Routh (2000). More recently, in a larger group of 16 juvenile Tawny Owls, Leighton et al (2008) reported a survival rate of at least 37% six weeks after release.…”
Section: Introductionmentioning
confidence: 55%
“…Their conclusion was that short-term survival (75%) was sufficient to justify the rehabilitation process. Csermely (2000a) tracked eight juvenile Tawny Owls for 7 -79 days, recorded only one death by predation and drew a similar conclusion to Bennett and Routh (2000). More recently, in a larger group of 16 juvenile Tawny Owls, Leighton et al (2008) reported a survival rate of at least 37% six weeks after release.…”
Section: Introductionmentioning
confidence: 55%
“…The debilitation state in which M1 was recovered allows for us to hypothesize that an inability to search for food after liberation is a possible cause. This could suggest that long detention periods can lead porcupines to develop addiction towards human-supplied feed, as also observed in wolves and birds [22][23][24][25][26][27][28]. Therefore, M1-post-liberation behavior could lead to other attributes as the causes of unsuccessful liberation.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, physical strength recovery (not only general weight regaining) is an actual fitness prerequisite that will determine the raptor’s fate in the wild, mainly in the first few days. Csermely [ 10 ], in fact, stresses that half of the released birds of prey die from starvation within one week of release.…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation standards and pre-release screening can be different from one rehabilitation center to another but usually, a rescued raptor is considered recovered after having regained weight, being able to fly, and completed a molt [ 8 , 10 , 11 ]. Although a short recovery period and quick release are always desirable, in case of prolonged hospitalization it could be useful to wait for a molt.…”
Section: Introductionmentioning
confidence: 99%